Steinert myotonic dystrophy: Family Studio - Voto Bernales, Jorge (1952)
Observations of a family of 8 patients presenting with Steinert disease, which coincide with most of the literature on this disease, as to confirm the "progressive heritage" as a feature, and the almost complete record of the symptomatic triad: atrophy, and cataract miotono. Males get sick more often than women and it is interesting that these symptoms have not been observed in isolation in other family members. They found at least two symptoms in the same individual, and characterizing the disease in different degrees of evolution. The frequent absence of endocrine disorders was also noted, except for alopecia in men and 2 women dysmenorrhea.